Mão de obra versus materiais: uma aplicação da curva de custo abc - Alves, Maria Augusta Rodrigues (Universidade Federal Rural do Semi-Árido, 2018)
In recent years, the construction industry has presented high potential in the Brazilian economic and political scenario. On the other hand, the importance related to the control of productivity costs in the sector is well known. Recent studies confirm the relevance of valuation tools regarding the physical and financial performance of buildings. Since, through the managerial employment of these instruments, it is possible to reduce production costs, as well as to improve issues related to deadlines and quality of services. Another issue that deserves attention is the composition of costs, that is, the relationship between material inputs and labor. Specifically, in Brazil several methods are used in order to obtain productive efficiency in the management of works, especially the activity-based costing method - ABC cost curve. The main objective of this study was to investigate the items with the greatest impact on the composition of costs related to the construction of a building located in the city of Rodolfo Fernandes - RN, in order to determine if the use of this cost management tool could reduce the total expenses of the work, and, consequently, increase the productivity. In addition, it was verified the relation between the costs with materials and hand of works comparing the existing literature. The most striking results show that, that is 6,6% of the components that compose the general expenditure of the project spend practically the costs of the São Paulo plaster, masonry of elevation, batatais gravels, planting of grass gravels, manual excavation of trench and precast slab half of all resources made available. In addition, the composition of total costs is in line with the Pareto principle. For, 23,07% of the items account for 80% of the overall cost of the work. In addition, it was found that 53,84% of the costs refer to labor expenditures, against 46,16% attributed to inputs and materials.
Keywords: Princípio de Pareto; Curva ABC; Composição dos custos; Pareto principles; ABC curve; Composition of cost; ENGENHARIAS::ENGENHARIA CIVIL